2017
DOI: 10.1139/apnm-2017-0262
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic state can define the ovarian response to environmental contaminants and medicinal plants

Abstract: Environmental contaminants and medicinal plants can affect reproductive processes. The aim of this study was to investigate the effect of maternal metabolic status on the response of mouse ovaries to the environmental contaminants benzene and xylene, as well as to extracts of the medicinal plant yucca. Ovaries isolated from normal-lean and slightly obese mice were cultured with or without 0.1% benzene or xylene for 24 h. Similarly, ovaries isolated from normal-lean, slightly obese, and significantly obese mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Women exposed to aromatic hydrocarbons (e.g., xylene) had reduced levels of luteinizing hormone (LH) [ 6 , 7 ], follicle-stimulating hormone (FSH), and prostaglandin [ 6 ], as well as pregnanediol 3-glucuronide (pd3G) and estrone 3-glucuronide (E13G) [ 7 ]. In vitro studies showed that xylene was able to affect proliferation, apoptosis, and the release of steroids, peptide hormones, and prostaglandins by cultured murine [ 8 ], porcine [ 9 , 10 , 11 ], and bovine [ 12 ] ovarian cells. The adverse effects on the ovary could be due to the ability of xylene to induce oxidative stress and to affect the production and reception of steroid hormones, as well as the intracellular regulators of ovarian cell proliferation and apoptosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women exposed to aromatic hydrocarbons (e.g., xylene) had reduced levels of luteinizing hormone (LH) [ 6 , 7 ], follicle-stimulating hormone (FSH), and prostaglandin [ 6 ], as well as pregnanediol 3-glucuronide (pd3G) and estrone 3-glucuronide (E13G) [ 7 ]. In vitro studies showed that xylene was able to affect proliferation, apoptosis, and the release of steroids, peptide hormones, and prostaglandins by cultured murine [ 8 ], porcine [ 9 , 10 , 11 ], and bovine [ 12 ] ovarian cells. The adverse effects on the ovary could be due to the ability of xylene to induce oxidative stress and to affect the production and reception of steroid hormones, as well as the intracellular regulators of ovarian cell proliferation and apoptosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of PCNA and bax in the cells was detected by immunocytochemistry, as described previously (Sirotkin et al, 2021; Štochmaľová et al, 2018; Tarko et al, 2020), by using primary monoclonal antibodies against these molecules (all from Santa Cruz Biotechnology, Inc., dilution 1:500), secondary swine antibodies against mouse IgG labelled with horseradish peroxidase (Servac, dilution of 1:1000) and visualized by staining with DAB substrate (Roche Diagnostics GmbH). According to the information of the manufacturer and our previous observations (Sirotkin et al, 2017, 2020, 2021; Štochmaľová et al, 2018; Tarko et al, 2020), these primary antibodies cross‐reacted with human, rat, murine, bovine, equine and porcine PCNA and bax. In some cases, the assay has been validated by these primary antibodies and secondary polyclonal goat antibodies against mouse IgGs labelled with the fluorescent marker fluorescein isothiocyanate (FITC; Santa Cruz Biotechnology, dilution 1:1000).…”
Section: Methodsmentioning
confidence: 79%
“…each at 10 μg/mL or combinations of toluene (0, 1, 10 or 100 ng/mL) + one of the plant additives listed above (10 μg/mL). These doses correspond to the doses of toluene that could be available in environmental wasted water (Mrowiec, 2014) and the effective doses of toluene (Sirotkin et al, 2020; Tarko et al, 2020) and plant extracts (Ohyama et al, 2003; Sirotkin et al, 2017, 2020, 2021; Štochmaľová et al, 2018) used in previous in vitro experiments. Plant extracts were first dissolved in 50 μL of DMSO to reach stock solutions of 1 mg/mL plant extract.…”
Section: Methodsmentioning
confidence: 94%
“…The E2 output by ovarian fragments of rabbits [74] and sheep [81] was not influenced markedly. The release of IGF-I by rabbit [15] or ovine [81] ovaries was inhibited, although not affected in mice ovaries [71]. This contradictory research shows that there could be species-specific actions of yucca on ovarian steroidogenesis and that these effects are dose-dependent (Table 1).…”
Section: Physiological Action Of Ovarian and Gonadotropic Hormmonesmentioning
confidence: 96%
“…It was found that yucca directly stimulated the release of P4 by porcine [73], rabbit [74], ovine [81], and murine [71] ovaries. The release of T was inhibited by yucca addition to cultured porcine granulosa cells [73], although it was not altered when added to rabbit [74] and ovine [81] ovarian fragments or mouse ovaries [71]. The E2 output by ovarian fragments of rabbits [74] and sheep [81] was not influenced markedly.…”
Section: Physiological Action Of Ovarian and Gonadotropic Hormmonesmentioning
confidence: 99%